Sex differences in lifespan extension with acarbose and 17‐α estradiol: gonadal hormones underlie male‐specific improvements in glucose tolerance and mTORC2 signaling. Issue 6 (22nd August 2017) - Garratt, Michael; Bower, Brian; Garcia, Gonzalo G.; Miller, Richard A.
Summary: Interventions that extend lifespan in mice can show substantial sexual dimorphism. Here, we show that male‐specific lifespan extension with two pharmacological treatments, acarbose (ACA) and 17‐α estradiol (17aE2), is associated, in males only, with increased insulin sensitivity and improved glucose tolerance. Females, which show either smaller (ACA) or no lifespan extension (17aE2), do not derive these metabolic benefits from drug treatment. We find that these male‐specific metabolic improvements are associated with enhanced hepatic mTORC2 signaling, increased Akt activity, and phosphorylation of FOXO1a – changes that might promote metabolic health and survival in males. By manipulating sex hormone levels through gonadectomy, we show that sex‐specific changes in these metabolic pathways are modulated, in opposite directions, by both male and female gonadal hormones: Castrated males show fewer metabolic responses to drug treatment than intact males, and only those that are also observed in intact females, while ovariectomized females show some responses similar to those seen in intact males. Our results demonstrate that sex‐specific metabolic benefits occur concordantly with sexual dimorphism in lifespan extension. These sex‐specific effects can be influenced by the presence of both male and female gonadal hormones, suggesting that gonadally derived hormones from both sexes may contribute to sexual dimorphism in responses to interventions that extend mouse lifespan.